Building Religious Characters Through a Biological Perspective - Deden Ibnu Aqil (Al-Hayat: Journal of Islamic Education, 2018)
Character education is the answer to addressing the problems of the nation's life at this time, through this education students will have a better attitude in accordance with the purpose of education which is to form a noble personality. to be a man of faith and devotion to God Almighty, noble, knowledgeable, capable, creative, independent, and a democratic and responsible citizen, as mandated in Law No. 20 of 2003 concerning the National Education System. Biology is a lesson that studies all living things in this world. Biology is also a science that can change one's mindset to be scientific because it uses rational, empirical and universal reasoning. Although universal, biology can also build religious characters that may not be universal. Because biology is also systematically told in the scriptures. Scripture justifies the natural processes that occur. Like the Koran is a divine revelation that can increase the faith and devotion of the faithful. So that biology can be one way to improve religious character other than worship activities, listening to lectures or reading books. The problem is how to see the relationship between biology and religious values ​​and how to build character values ​​through biology. The improvement of religious character through biology is by providing additions to biological material with the holy verses of the Koran which are relevant to the content of the discussion on the biological material. As the discussion on reproductive material is related to the Al-Quran verse Al-Mu'minun verse 14 and the material for the classification of living things is explained in Al-Quran Surat An-nur verse 5.Pendidikan karakter menjadi jawaban menyikapi problematika kehidupan bangsa saat ini, melalui pendidikan ini siswa akan memiliki sikap yang lebih baik sesuai dengan tujuan pendidikan yaitu membentuk kepribadian yang berahlak mulia. menjadi manusia yang beriman dan bertaqwa kepada Tuhan Yang Maha Esa, berakhlak mulia, berilmu, cakap, kreatif, mandiri, dan menjadi warga negara yang demokratis serta bertanggung jawab, seperti yang diamanatkan dalam UU no 20 tahun 2003 tentang Sistem Pendidikan Nasional. Biologi adalah pelajaran yang mempelajari seluruh mahluk yang hidup di alam ini.Biologi juga merupakan ilmu yang dapat merubah pola pikir seseorang menjadi ilmiah karena menggunakan nalar rasional, empirikdan juga bersifat universal.Walaupun bersifat universal, biologi juga dapat membangun karakter religius yang mungkin tidak universal.Karena biologi juga diceritakan secara sistematis di dalam kitab suci. Kitab suci menjadi pembenaran akan proses alami yang terjadi. Seperti Al-Quran merupakan wahyu ilahi yang dapat meningkatkan keimanan dan ketaqwaankaum beriman.Sehingga biologi dapat menjadi salah satu cara meningkatkan karakter religius selain dari pada kegiatan ibadah, mendengarkan ceramah atau membaca buku. Permasalahannya adalah bagaimana melihat hubungan biologi dengan nilai religius dan bagaimana caramembangun nilai karakter melalui biologi. Peningkatan karakter religius melalui biologi adalah dengan memberikan penambahan pada materi biologi dengan ayat-ayat suci Al-Quran yang relevan dengan konten pembahasan materi biologi tesebut. Seperti pembahasan materi reproduksi dikaitkan dengan ayat Al-Quran surat Al-Mu’minun ayat 14dan materi klasifikasi mahluk hidup ada penjelasannya dalam Al-Quransurat An-nur ayat 5.